Design of Tri-frequency Combiner Based on Inverted T-stub Combiner Network - LIU Zirui; WANG Haoyu; HUANG Kama (工程科学与技术)
ObjectiveWith the rapid advancement of 5G communications, the Internet of Things (IoT), and smart radar systems, microwave transmission systems must support multi-band cooperative operation to enhance spectrum utilization efficiency. However, traditional designs employing independent hardware components for processing signals in different frequency bands result in bulky systems and exponentially increased costs. This necessitates the adoption of "heterodyne power combining technology", whose core objective is to achieve efficient synthesis of multi-band signals while minimizing mutual interference, thereby resolving the challenges of spectrum scarcity and hardware redundancy through effective signal synthesis and isolation. The practical hardware implementation of this technology is the heterodyne combiner, which merges signals of multiple frequencies into a single physical channel (e.g. transmission lines or antennas). Combiner circuits primarily adopt two structural forms: cavity-based and microstrip-based. Although cavity combiners exhibit lower insertion loss and higher power capacity, their large size and high manufacturing costs hinder their application in modern compact systems. In contrast, microstrip combiners are widely used in small-to-medium microwave transmission systems with less stringent power requirements due to their compact size, high integration, low fabrication cost, and consistency. A microstrip combiner typically consists of bandpass filters and a combining network, where the latter ensures isolation between two or more channels. Traditional T-shaped combining networks, however, face technical limitations when synthesizing cross-octave signals (e.g. a frequency ratio exceeding 6:1 between low and high bands). Influenced by parasitic passbands in microstrip bandpass filters, these networks commonly suffer from insufficient port isolation and abrupt increases in insertion loss. Moreover, simple T-shaped networks cannot simultaneously isolate three or more frequencies using a single stub, rendering them inadequate for synthesizing more than three frequency bands. This study aims to overcome the physical constraints of traditional structures by proposing a novel combining network design that enables efficient synthesis of multi-band and cross-octave signals, addressing the urgent demand for combiners with multi-frequency support, wide bandwidth, low loss, and high isolation in modern microwave systems.MethodsThis study proposes an innovative combiner network architecture based on inverted T-shaped stubs, comprising a notch network and an impedance matching network. Functionally, the notch network isolates channels by creating impedance nulls at specific frequencies, while the matching network ensures broadband impedance matching between the bandpass filters and the notch network, thereby guaranteeing low-loss transmission of in-band signals. The core operating principle can be described as follows: the notch network precisely adjusts the characteristic impedance and electrical length of the inverted T-shaped stubs, inducing a short-circuit impedance characteristic at the target isolation frequencies. Combined with the impedance transformation of λ/4 transmission lines, this design achieves an equivalent open-circuit state at the corresponding combiner ports. This methodology offers two significant advantages: First, the isolation mechanism is independently realized by the notch network, effectively avoiding the adverse effects of parasitic passbands in traditional bandpass filters. This enables channel isolation across multiple octaves (e.g. 915 MHz to 5.8 GHz, a 6.34:1 ratio). Second, through scalable topological design, a single channel can integrate multiple notch units to achieve simultaneous isolation of multi-band signals, meeting the complex isolation requirements of multi-frequency combining systems.ConclusionsThis study proposes a novel combining network based on inverted T-shaped stubs and demonstrates its application in a triplex combiner. The innovative design addresses technical challenges in cross-octave signal synthesis and poor isolation during multi-frequency combining. Measured data confirm excellent performance in insertion loss, channel isolation, and operational bandwidth, particularly suited for complex scenarios requiring simultaneous processing of ISM and WiFi band signals. For instance, it enables precise multi-band energy synthesis in intelligent microwave hyperthermia systems, supports multi-protocol parallel communication in IoT devices, and facilitates wideband interference in drone countermeasures. The research outcomes provide a robust technical solution for multi-band device integration in multi-frequency signal transmission systems and industrial IoT (IIoT) applications, holding significant engineering value. However, it should be noted that the proposed combining network suffers from increased PCB dimensions and compromised structural compactness when operating at lower frequencies or with excessive channels. Consequently, further investigation into miniaturization strategies for this network remains imperative.